2009
DOI: 10.1111/j.1464-410x.2009.08378.x
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between total and free serum testosterone and the risk of prostate cancer and tumour aggressiveness

Abstract: > 4.0 ng/mL. Tumour aggressiveness was assessed according to serum PSA level, biopsy Gleason score and clinical stage in the subset of 216 patients with cancer (45.2%). We also compared prostate cancer risk and tumour aggressiveness in 80 hypogonadal patients (16.7%) and 398 eugonadal patients (83.3%). RESULTSThe median total serum testosterone level in patients without and with prostate cancer was 466.0 and 466.5 ng/dL, respectively ( P > 0.05); the median levels of free serum testosterone were 9.9 and 10.0 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 24 publications
1
36
0
Order By: Relevance
“…Salonia et al 12 found an association between androgens and higher risk PCa that was not proven to be independent on multivariate analysis. Other studies showed no association, 12,24 while Porcaro et al suggest a direct relation between testosterone levels and Gleason score, a result that opposes the findings described previously. 25 In our study, we evaluated 423 patients and tested two thresholds, 250 and 300 ng/dL, for the definition of hypogonadism.…”
Section: Discussionmentioning
confidence: 61%
“…Salonia et al 12 found an association between androgens and higher risk PCa that was not proven to be independent on multivariate analysis. Other studies showed no association, 12,24 while Porcaro et al suggest a direct relation between testosterone levels and Gleason score, a result that opposes the findings described previously. 25 In our study, we evaluated 423 patients and tested two thresholds, 250 and 300 ng/dL, for the definition of hypogonadism.…”
Section: Discussionmentioning
confidence: 61%
“…Even though the association between T and erectile function has not been completely clarified [19][20] and the role of T in PCa development is still under investigation, 21,22 our study investigated the relationship between T and ED in men with PCa, before RP. Our data seem to be in agreement with the conclusions of Khera,23 suggesting that although the relationship between testosterone and improvement in erectile function should be well established, the role of testosterone in ED recovery after RP may be of even greater significance.…”
Section: Discussionmentioning
confidence: 99%
“…14 IIEF was used to better define the erectile function. The possible scores for the IIEF-5 range from 5 to 25, and ED was classified into five categories based on the scores: severe (5-7), moderate (8)(9)(10)(11), mild to moderate (12)(13)(14)(15)(16), mild (17)(18)(19)(20)(21) and no ED (22)(23)(24)(25). 15 …”
Section: Hrqol Measuresmentioning
confidence: 99%
“…However, in a IGF-1 levels correlate with sexual dysfunction AW Pastuszak et al recent study of 478 men screened for prostate cancer with transrectal ultrasound-guided biopsy, no relationship was observed between serum testosterone level and prostate cancer severity. 43 Thus, it is possible that the relationship between testosterone level and Gleason score is indeed most significant in older men with more aggressive tumors. Our study was limited by several factors.…”
Section: Discussionmentioning
confidence: 99%